Association study of NDST3 gene for schizophrenia, bipolar disorder, major depressive disorder in the Han Chinese population. Issue 1 (15th November 2017) - Wang, Lin; Chen, Jianhua; Li, Zhiqiang; Sun, Weiming; Chen, Boyu; Li, Sining; Li, Weidong; Lu, Dajiang; Wang, Yonggang; Shi, Yongyong
Abstract : The NDST3 gene at 4q26 was a functional candidate gene for mental disorders. Recently, a novel genome‐wide significant risk locus at chromosome 4q26 was identified and the top single nucleotide polymorphism rs11098403 in the vicinity of NDST3 gene was reported to confer risk of schizophrenia in Caucasian. Nevertheless, association between NDST3 gene polymorphisms and schizophrenia, bipolar disorder, or major depressive disorders has not been well studied in the Han Chinese population. To further investigate whether NDST3 is a risk gene for these mental disorders, we genotyped and analyzed eight tag SNPs (rs11098403, rs10857057, rs2389521, rs4833564, rs6837896, rs7689157, rs3817274, rs609512) covering NDST3 gene in 1, 248 schizophrenia cases, 1, 056 major depression cases, 1, 344 bipolar disorder cases, and 1, 248 controls of Chinese origin. However, there was no significant difference in allelic or genotypic frequency observed between each case group and healthy controls. Accordingly, our study does not support that the NDST3 gene plays a major role in schizophrenia, bipolar disorder, and major depressive disorder in the Han Chinese population.